Cashing in on ATM malware: a comprehensive look at various attack types - Sancho, David (Europol European Cybercrime Centre, 2017)
ATM malware is one of the digital threats that have been around for a while now, with the discovery of the first known variant dating back to 2009. It should not be a surprise that it has become a mainstay in many cybercriminals’ arsenal because it can, plainly put, steal cold, hard cash. Trend Micro Forward-Looking Threat Research (FTR) Team and Europol’s European Cybercrime Centre (EC3)